If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 60 + -1(3x + 6) = 3(x + 4) + x Reorder the terms: 60 + -1(6 + 3x) = 3(x + 4) + x 60 + (6 * -1 + 3x * -1) = 3(x + 4) + x 60 + (-6 + -3x) = 3(x + 4) + x Combine like terms: 60 + -6 = 54 54 + -3x = 3(x + 4) + x Reorder the terms: 54 + -3x = 3(4 + x) + x 54 + -3x = (4 * 3 + x * 3) + x 54 + -3x = (12 + 3x) + x Combine like terms: 3x + x = 4x 54 + -3x = 12 + 4x Solving 54 + -3x = 12 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 54 + -3x + -4x = 12 + 4x + -4x Combine like terms: -3x + -4x = -7x 54 + -7x = 12 + 4x + -4x Combine like terms: 4x + -4x = 0 54 + -7x = 12 + 0 54 + -7x = 12 Add '-54' to each side of the equation. 54 + -54 + -7x = 12 + -54 Combine like terms: 54 + -54 = 0 0 + -7x = 12 + -54 -7x = 12 + -54 Combine like terms: 12 + -54 = -42 -7x = -42 Divide each side by '-7'. x = 6 Simplifying x = 6
| 2.7x=-4 | | 12n(p+3)= | | 3t+2t+7=32 | | 4x^2-5y^2-20=0 | | 9e^6x=2 | | -8m-7m= | | (11+7y)9= | | -6-6(3n-4)=162 | | 9t^2-12t-5= | | 0.25q+0.10(2q+6)=11.85 | | 15x-7=0 | | -3(5-6X)=-15 | | m-4m=2m | | (H+8)5= | | 7x-15+2x=3+9x-17 | | 72x+436=-96x+1108 | | 8x-11=x-6x+8 | | 5katie+7katie=12 | | -(x+2)=4 | | 1=7k-6k | | 3(-5x-8)=-159 | | 4-3(2c-2)=11c | | 8x+2x=90 | | x+14+5x+2=121 | | 4p-5+2p=7+5p+2 | | 0.5y+6=y-4 | | 2m(m+3)-6(3m-2)+2=0 | | 7t-t-7=5t-8 | | (6a^2-2a-7)+(4a^2+2a-4)= | | 5katie+7katie=13 | | 7q-(q-2)=4Q+2(q+1) | | (4x-1)+(x+11)+90=180 |